Biodegradable high-strength medical soft tissue adhesive as well as preparation method and application thereof

By using raw materials such as polyethylene glycol and isocyanate, a biodegradable high-strength medical soft tissue adhesive was prepared, which solved the problem of insufficient bond strength and biodegradability in the prior art, and achieved high strength, rapid curing and Good biocompatibility effect.

CN119463089APending Publication Date: 2025-02-18NUOYIMEIER (SHANDONG) MEDICAL TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411362574.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing medical soft tissue adhesives have shortcomings in terms of bonding strength and biodegradability. The fiber adhesive has poor bonding strength and high immunity risk. The cyanoacrylate adhesive has a high hardness and is not degradable after curing. PolyB The swelling rate of glycol adhesives is high and may cause postoperative complications.

Method used

Using raw materials such as polyethylene glycol, isocyanate, hard-segment electroneutral chain extender and hard-segment ionized chain extender, biodegradable high-strength medical soft tissue adhesive is prepared through a one-pot reaction, and the ratio of soft-segment is adjusted to Improve the mechanical properties and biocompatibility of the adhesive.

Benefits of technology

It significantly improves the bonding strength and biodegradability of the adhesive, shortens the curing time, reduces internal friction and tissue compression, and improves the biocompatibility and clinical application safety of the adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463089A_ABST
    Figure CN119463089A_ABST
Patent Text Reader

Abstract

The invention relates to a biodegradable high-strength medical soft tissue adhesive as well as a preparation method and application thereof. The medical soft tissue adhesive comprises a soft segment, a hard segment and a hard segment chain extender, the soft segment is a polyethylene glycol polymer; the hard segment is isocyanate; the hard segment chain extender comprises a hard segment electrically neutral chain extender and a hard segment ionized chain extender; the molar ratio of the polyethylene glycol polymer to the isocyanate to the hard segment electrically neutral chain extender to the hard segment ionized chain extender is (1-7): (50-95): (14-20): (2-6). The preparation method comprises the following steps: mixing the polyethylene glycol polymer, the hard segment chain extender and the isocyanate, heating and reacting to obtain a mixed reaction system; cooling after the reaction is completed, adding a rheology modifier, a foaming catalyst and a stabilizer into the mixed reaction system, and uniformly mixing to obtain the biodegradable high-strength medical soft tissue adhesive which is suitable for functional composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical technology, and in particular to a biodegradable high-strength medical soft tissue adhesive and a preparation method and application thereof. Background Art

[0002] Minimally invasive surgery has been increasingly used in recent decades. Due to the limited operating space in minimally invasive surgery, the treatment methods for soft tissue trauma closure have gradually evolved from traditional sutures, fixation nails and other solutions to convenient bonding technology. Bonding is simple and convenient, so it has been increasingly widely used in clinical practice.

[0003] At present, the medical adhesives commonly circulated in the domestic and international markets are mainly divided into three categories: fibrin glue (FS), cyanoacrylate adhesive (CA) and polyethylene glycol-based tissue glue (PEG).

[0004] Fibrin-based bioadhesives have good degradation properties, but their bonding strength is relatively poor (103-104 Pa). They are not suitable for bonding clinical soft tissues, but are more widely used for occlusion after suturing. In addition, this type of adhesive also has a certain degree of immune risk, which also limits its clinical application.

[0005] Cyanoacrylate adhesives have been on the market for decades. They are the most widely used medical adhesives due to their rapid curing, high bonding strength, low cost, and inherent bactericidal properties. However, they are very hard after curing and have a strong foreign body sensation. In addition, these adhesives are not biodegradable. As foreign bodies, they are easily prone to persistent tissue inflammation when left in the body for a long time. At the same time, they form permanent tissue occupancy, which is not conducive to the repair of soft tissues.

[0006] Polyethylene glycol adhesives have good biocompatibility and certain tissue adhesion, but they have a high swelling rate and are prone to compressing blood vessels and nerves around tissues, causing other postoperative complications. The strength of the swollen polyethylene glycol hydrogel itself is also easily reduced significantly, making it only suitable for short-term wound closure. Summary of the invention

[0007] The purpose of the present invention is to provide a biodegradable high-strength medical soft tissue adhesive and a preparation method and application thereof, so as to significantly improve the comprehensive performance of the medical soft tissue adhesive.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is: The first aspect of the present invention provides a biodegradable high-strength medical soft tissue adhesive, which is made by reacting raw materials, wherein the raw materials include a soft segment monomer, a hard segment monomer and a hard segment chain extender; The soft segment monomer is selected from polyethylene glycol or its methoxy derivatives, and has an average molecular weight of 300 to 1000; The hard segment monomer is isocyanate; The hard segment chain extender is a mixture of a hard segment electrically neutral chain extender and a hard segment ionized chain extender; The molar ratio of the soft segment monomer, the hard segment monomer, the hard segment electrically neutral chain extender and the hard segment ionized chain extender is (1-7): (50-95): (14-20): (2-6).

[0009] Furthermore, the isocyanate is ethyl lysine diisocyanate and its derivatives or 1,4-diisocyanatobutane and its derivatives.

[0010] Furthermore, the hard segment electrically neutral chain extender is an amino acid small molecule chain extender, and the amino acid small molecule chain extender is a mixture of one or more selected from serine, lysine, cystine, serinol, N-acetylneuraminic acid, dipeptide and amino acid ester derivatives; The hard segment ionized chain extender is a quaternary ammonium salt small molecule chain extender, and the quaternary ammonium salt small molecule chain extender is a mixture of one or more selected from bis(2-hydroxyethyl)dimethylammonium chloride, 1,3-dihydroxymethyl-5,5-dimethylhydantoin, 3-(2,3-dihydroxypropyl)-5,5-dimethylimidazolidine-2,4-dione, N-methyldiethanolamine, N-ethyldiethanolamine, 2,3-dihydroxypropyl-trimethylammonium chloride and proiodine.

[0011] Furthermore, the raw materials also include a rheology regulator, a foaming catalyst and a stabilizer. The amount of the rheology regulator is 30-50% of the total mass of the soft segment monomer and the hard segment monomer; the amount of the foaming catalyst is 0.8-1.2% of the total mass of the soft segment monomer and the hard segment monomer; the amount of the stabilizer is 0.01-0.05% of the total mass of the soft segment monomer and the hard segment monomer.

[0012] Furthermore, the rheology regulator is a mixture of one or more selected from pentafluorobutane, heptafluoropropane, perfluorohexanone, chlorotrifluoropropylene and hexafluorobutene; the stabilizer is a mixture of one or more selected from pyruvic acid, dimethyl sulfoxide, propylene glycol methyl ether acetate, triethyl citrate, sulfuric acid, hydrochloric acid and phosphoric acid.

[0013] Furthermore, the foaming catalyst is at least one selected from an organic amine catalyst and an organic metal catalyst, the organic amine catalyst is a mixture of one or more selected from triethylenediamine, bis(dimethylaminoethyl) ether and bis(morpholine) diethyl ether; the organic metal catalyst is a mixture of one or more selected from stannous octoate, dibutyltin dilaurate, organic bismuth salts and organic antimony salts.

[0014] The second aspect of the present invention provides a method for preparing a biodegradable high-strength medical soft tissue adhesive, comprising the following steps: S1: mixing the soft segment monomer, the hard segment chain extender and the hard segment monomer and heating them to react to obtain a mixed reaction system; S2: After the reaction is complete, the temperature is lowered, and a rheology regulator, a foaming catalyst and a stabilizer are added to the mixed reaction system. After uniform mixing, the biodegradable high-strength medical soft tissue adhesive is obtained.

[0015] Furthermore, in step S1, the mixing heating temperature is 75-85° C., and the heating reaction time is 1-2 hours.

[0016] Furthermore, in step S2, the cooling temperature is 15-20°C.

[0017] The third aspect of the present invention provides an application of a biodegradable high-strength medical soft tissue adhesive in a functional composite material.

[0018] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: The present invention accelerates the transfer of water vapor molecules by introducing polyethylene glycol hydrophilic channels, greatly shortening the curing time; the introduction of ionized chain extension centers enhances the electrical interaction between the adhesive and the soft tissue on the wound surface, thereby greatly improving the interfacial bonding strength, and achieving the characteristics of the adhesive having both high bonding strength and short curing time. Secondly, by adjusting the ratio of soft and hard segments, an adhesive with adjustable mechanical properties can be obtained, which has excellent biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings: Figure 1 A shear bonding model diagram of a sample in an in vitro bonding experiment provided in the present invention; Figure 2 This is a comparison chart of the control surgery group and the glue injection bonding group in the rabbit nasal mucosa closure experiment provided in the present invention; Figure 3This is a histopathological picture of the adhesive provided in the present invention seven days after implantation; Figure 4 It is a data diagram of the swelling rate of the adhesive in Examples 6, 7 and 8 provided in the present invention; Figure 5 The diagrams are cell compatibility test diagrams of the positive control, negative control and adhesives of Examples 4 to 8 provided in the present invention; Figure 6 It is a degradation mass loss data diagram provided in the present invention; Figure 7 A diagram showing pH changes during the degradation process provided in the present invention; Figure 8 The NMR spectrum of Example 1 provided in the present invention; Fig. 9 The NMR spectrum of Example 2 provided in the present invention; Fig.10 The NMR spectrum of Example 3 provided in the present invention; Fig.11 The NMR spectrum of Example 4 provided in the present invention; Fig.12 is the NMR spectrum of Example 5 provided in the present invention; Fig.13 The NMR spectrum of Comparative Example 1 provided in the present invention; Fig.14 It is the NMR spectrum of Comparative Example 2 provided in the present invention; Fig.15 The infrared spectra of Examples 1 to 5 and Comparative Example 1 provided in the present invention are shown in FIG. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Embodiment 1: This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof, comprising the following steps: S1: Trimethylolpropane and bis(2-hydroxyethyl)dimethylammonium chloride were vacuum dried at 50°C for more than 2 h, and polyethylene glycol 400 was vacuum dehydrated at 110°C for 2 h; Place dried trimethylolpropane (1.96 g, 14.6 mmol), bis(2-hydroxyethyl)dimethylammonium chloride (0.713 g, 4.2 mmol) and polyethylene glycol 400 (1.36 g, 3.4 mmol) in a 100 ml three-necked flask, replace with nitrogen for more than three times, heat at 75 °C and stir to dissolve the homogeneous phase (dissolution time is about 30 min); Then, lysine ethyl ester diisocyanate (13.681 g, 60.5 mmol) was slowly added dropwise to the above mixed system, and the reaction was continued for 1 h after the addition was completed; S2: The reaction endpoint is confirmed by titrating isocyanate with di-n-butylamine method. After the reaction reaches the endpoint, the temperature of the mixed reaction system is lowered to below 15°C, and then pentafluorobutane (8.9 g, 60.1 mmol) is added to the reaction system, stirred until homogeneous, and then bismorpholine diethyl ether (190 µL) is added, and stirring is continued for 15 min. Then, sulfuric acid (17.8 mg) is added and stirring is continued for 30 minutes. The mixture is allowed to stand for defoaming to obtain a light yellow clear viscous liquid, which is the biodegradable high-strength medical soft tissue adhesive.

[0022] Embodiment 2: This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the selected amino acid small molecule chain extender is serinol.

[0023] Embodiment 3: This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof. The only difference between the embodiment 1 and the embodiment 1 is that the selected amino acid small molecule chain extender is a combination of serinol and lysine, the amount of serinol used is (1.33g, 14.6mmol); the amount of lysine used is (0.292g, 2.0mmol); the amount of lysine ethyl diisocyanate used is (14.609g, 64.6mmol); the amount of pentafluorobutane used is 9.5g; the amount of bismorpholine diethyl ether used is 203µL; and the amount of sulfuric acid used is 19mg.

[0024] Embodiment 4: This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the selected amino acid small molecule chain extender is serinol and the selected soft segment monomer is polyethylene glycol 800.

[0025] Embodiment 5: This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the soft segment monomer selected is polyethylene glycol 600.

[0026] Embodiment 6: This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the selected amino acid small molecule chain extender is serinol and the selected soft segment monomer is polyethylene glycol 600.

[0027] Embodiment 7: This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof, which is different from Example 1 only in that the selected amino acid small molecule chain extender is serinol, the selected soft segment monomer is polyethylene glycol 600, and the selected amount of lysine ethyl ester diisocyanate is (15.750 g, 69.62 mmol).

[0028] Embodiment 8: The present embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof, which is different from Example 1 only in that the selected amino acid small molecule chain extender is serinol, the selected soft segment monomer is polyethylene glycol 600, and the feeding amount of polyethylene glycol 600 is (2.40 g, 4.0 mmol); the feeding amount of the selected lysine ethyl ester diisocyanate is (13.959 g, 61.7 mmol).

[0029] Example 9 This embodiment provides a biodegradable high-strength medical soft tissue adhesive and a preparation method thereof. The only difference between the embodiment 1 and the embodiment 1 is that the selected amino acid small molecule chain extender is serinol, the selected soft segment monomer is polyethylene glycol 600, the selected amount of lysine ethyl ester diisocyanate is (15.750 g, 69.62 mmol), and the used rheology modifier is monochlorotrifluoropropylene.

[0030] Comparative Example 1 This embodiment provides a medical soft tissue adhesive and a preparation method thereof, which is different from Example 1 only in that the selected amino acid small molecule chain extender is serinol, no soft segment monomer is selected, and the selected amount of lysine ethyl ester diisocyanate is (13.059 g, 57.7 mmol).

[0031] Comparative Example 2 This embodiment provides a medical soft tissue adhesive and a preparation method thereof, which is different from Example 1 only in that the selected amino acid small molecule chain extender is serinol, and the quaternary ammonium salt small molecule chain extender is not selected, the selected soft segment monomer is polyethylene glycol 600, and the selected amount of lysine ethyl ester diisocyanate is (12.730 g, 56.3 mmol).

[0032] In the present invention, the medical soft tissue adhesive prepared in the above-mentioned embodiments and comparative examples is tested and characterized for performance, and the specific test methods and results of each performance are characterized as follows: 1. In vitro bonding test According to the YY / T 0729.1-2009 standard, the in vitro bond strength is obtained by shear bond test. The shear bond model is as follows: Figure 1 As shown, The specific test steps include: (1) Sample preparation Remove the fat layer and epidermis from fresh pig skin, cut it into (2.5±0.1cm)×(10±0.2cm) sizes, of which 9.0cm is non-adhesive and 1.0cm is adhesive, put it into a plastic bag (two adherend samples are required as samples for each test), and keep it wet with phosphate buffered saline (PBS, PH=7.3) at all times and place it in a 37℃ water bath or environmental chamber.

[0033] (2) Sample preparation Take out the tissue sample from the plastic bag and wet the surface of the sample with new gauze; then evenly apply an appropriate amount of adhesive to the bonding area; bond the two tissue surfaces of a pair of test fixtures together and form a straight line so that the overlap meets the requirements; then cover the bonded sample with gauze with phosphate buffer and apply a force of about 1N~2N on each group of sample pieces for 30 minutes; after the adhesive is cured, measure and record the width and length of the bonding area (accurate to 0.05cm).

[0034] (3) Sample processing Cover the tissue again with gauze soaked in phosphate buffer, put the sample back into the plastic bag and return to the constant temperature environment. The adhesive curing time is at least 30 minutes. The curing conditions are (37 ± 2) ° C and (50 ± 5)% relative humidity. The tissue sample must be kept wet during the whole process to prevent shrinkage due to drying.

[0035] (4) Experimental procedures See also Figure 1 , place the sample in the fixture of the testing machine, and load the sample with the crosshead at a speed of 5mm / min until it is damaged.

[0036] (5) Calculation Calculate the bonding area to an accuracy of 0.05 cm 2 The lap-shear tensile bearing strength was calculated by dividing the maximum load by the bond area and the result was expressed in kilopascals (KPa). The average lap-shear tensile bearing strength was calculated for each sample.

[0037] Table 1 Comparison of in vitro bonding strength (KPa) of various embodiments and comparative examples It can be seen from Table 1 that the bonding strength of the adhesive formula involved in the embodiment is much greater than the bonding strength of the fibrin glue adhesive (Compxin). At the same time, the comparison between Comparative Examples 1 and 2 and Examples 1-9 also reflects the contribution of polyethylene glycol and quaternary ammonium salt to the bonding strength of the adhesive system, thereby verifying the synergy of polyethylene glycol and quaternary ammonium salt in enhancing mechanical strength.

[0038] From the comparison of Examples 1, 2, and 3, it can be seen that the amount of amide bonds introduced also has a great influence on the bonding strength. Since the reactivity of isocyanate with amino groups is higher than that of hydroxyl groups, there are great differences in the elementary structures of the adhesive prepolymers. The appropriate amount of amide bonds introduced can balance the contradiction between the mechanical strength and biodegradation rate of the adhesive.

[0039] From the comparison of Examples 2, 4, and 6, it can be seen that the bonding strengths of polyethylene glycol chains with the same molar amount but different lengths are different.

[0040] From the comparison of Examples 6, 7, and 8, it can be seen that different addition amounts of polyethylene glycol affect the bonding strength, thus providing a reliable idea for balancing the bonding strength and biodegradation rate for subsequent clinical use.

[0041] From the comparison between Examples 7 and 9, it can be seen that different fluorocarbon rheology modifiers can not only affect the shelf life of the adhesive, but also affect the wettability of the adhesive to the biological tissue substrate, thereby affecting the interfacial bonding strength of the adhesive.

[0042] 2. Elongation at break test (1) Sample preparation Take about 7.7g of adhesive and inject it into a glass culture dish (outer diameter 10cm, inner diameter 9.5cm), cast into a film, and put it into a constant temperature and humidity chamber for curing. The curing conditions are (37±2)℃ and (50±5)% relative humidity. It takes about 7 hours to cure to constant weight, and then put it into a vacuum drying oven at 37℃ to continue drying to constant weight, which takes about 4 hours. After the constant weight of the film is removed from the glass culture dish, cut it into a rectangular strip with a width of 15mm and a length of 50mm from the middle, and cut at least three samples; (2) Sample testing Load the sample into the fixture of the electronic universal testing machine, set the speed to 25mm / min, make the effective length 30mm, start the operation, and record the displacement when the sample breaks. The calculation formula is as follows: Elongation at break (%) = La / L0×100% Where: La—displacement when the sample breaks, unit: mm; L0—original length of the sample (effective length): 30 mm; (3) Elongation at break test of cyanoacrylate The film formation of cyanoacrylate glue (the company's own product: Pinyu® medical glue) refers to step (1); the test refers to step (2), and the elongation at break of the film-formed sample is tested. The test data are shown in Table 2: Table 2 Elongation at break Example 1 Example 4 Example 6 Example 7 Example 8 Comparative Example 1 Medical glue Elongation at break 54.2% 94.7% 76.8% 69.4% 83.2% 14.9% 1.3% It can be seen from the data in Table 2 that, compared with cyanoacrylate medical adhesives, the elongation at break of the adhesive in the embodiments of the present invention is significantly improved. The reason is that the flexible polyethylene glycol chain segments are introduced into the adhesive, thereby improving the toughness of the material, reducing the internal friction of the closed wound surface, and reducing the possibility of causing inflammation and tissue damage.

[0043] From the comparison of Examples 1, 4, and 6, it can be seen that the elongation at break of equimolar polyethylene glycol homologues gradually increases with the increase of molecular weight, which also proves that the flexible polyethylene glycol chain is a key factor in improving the toughness of the adhesive film; from the comparison of Examples 6, 7, 8 and Comparative Example 1, it can be seen that the molecular weight of fixed polyethylene glycol increases with the increase of the amount of polyethylene glycol introduced, and the elongation at break also gradually increases.

[0044] 3. Lap shear strength data for other soft tissue substrates The medical soft tissue adhesive prepared in Examples 2, 4, 6, 7, and 8 was applied to fresh porcine small intestines. The sample preparation and testing methods were as follows: (1) Sample preparation Wash the pig small intestine with phosphate buffer (pH=7.3), cut it into 2.5±0.1cm×2.5±0.1cm slices, put it into a plastic bag (two adherend samples are required as sample slices for each test), keep it wet with phosphate buffer (PBS, pH7.3), and place it in a 37℃ water bath or environmental chamber.

[0045] (2) Sample preparation Take out the tissue sample from the plastic bag and use new gauze to dry the sample surface. Then use cyanoacrylate glue to bond the outer surface of the pig intestine to two T-shaped clamps respectively, and cure for about 3-5 minutes. Then apply an appropriate amount of adhesive evenly to the bonding area on the inner surface of a pig intestine. Bond the inner surfaces of the two small intestines of a pair of test fixtures together, paying attention to keep the two fixtures aligned and keep the docking without misalignment. Then cover the bonded sample with gauze with phosphate buffer and apply a force of about 1N~2N on each group of sample pieces, and place them in a 37℃ constant temperature box for 30 minutes. Finally, measure and record the width and length of the bonding area (accurate to 0.05cm).

[0046] (3) Sample disposal All samples should be stabilized at the test temperature for 15 minutes before the test. To make the test comparable, the test conditions should be (23±2)℃ and (50±5)% relative humidity. The tissue samples must be kept wet throughout the process to prevent shrinkage due to drying.

[0047] (4) Experimental procedures Place the sample in the fixture of the testing machine so that the force direction is perpendicular to the bonding surface. Load the sample with the crosshead at a speed of 2 mm / min until it is damaged.

[0048] (5) Calculation Record the maximum load at failure, and calculate the tensile strength by dividing the maximum load (in Newton) by the bonding area of ​​the specimen. And calculate the average tensile strength of the selected samples. The experimental data are as follows: Table 3 In vitro bonding strength (KPa) Instance Name 2 4 6 7 8 Tensile Strength 19.7 28.9 32.6 16.6 25.4 By comparing the data in Table 1 and Table 3, it can be seen that as the soft tissue substrate changes from the more hydrophobic pig skin surface to the more hydrophilic small intestinal mucosa surface, the same adhesive formula shows completely different mechanical strength trends. That is, the different contents of hydrophilic components (PEG, quaternary ammonium salts, etc.) in the adhesive structure and the different elementary structures lead to different connection methods of the raw materials in the chain segments, which makes the adhesive show different wettability to the soft tissue substrate, and finally affects the effective bonding area of ​​the bonding interface, so that the bonding strength of the adhesive to different substrate interfaces changes.

[0049] Therefore, the purpose of adjustable biomechanical properties can be achieved by screening different raw materials or adjusting the ratio of soft and hard segments, so that it can be used for different soft tissue interfaces.

[0050] 4. Rabbit nasal mucosal closure experiment Ordinary New Zealand white rabbits were taken, weighed, anesthetized, and the hair above the rabbit nasal bone was removed with a razor, and the skin was prepared by iodine disinfection. A vertical incision was made in the rabbit nasal bone epidermis along the midline of the nose with a scalpel and surgical scissors, and the rabbit nasal septum covering bone piece at 4.0cm from the rabbit nose was drilled with a 0.6cm diameter circular bone drill, and the rabbit nasal septum mucosa and cartilage were peeled off with microscopic tweezers, and microscopic scissors were used to remove 0.5cm long and 0.5cm deep nasal septum cartilage in the operation area, and 0.05ml (1-2 drops) of the adhesive glue of Example 1 that had been irradiated and sterilized was drawn with a sterile syringe and injected into the middle of the bilateral mucosa of the nasal septum in the operation area, and the bilateral mucosa was clamped and bonded with microscopic hemostatic clips, and the colloid curing time was recorded, and it was difficult to pull the wound mucosa with tweezers, and the curing time was recorded, and three experimental subjects were grouped, and the curing time was averaged.

[0051] See also Figure 2In the pictures of the control surgery group and the glue injection bonding group, the average closure time of the rabbit nasal septum nasal mucosa is between 3-5 minutes, but the hemostatic clip can be removed from the rabbit nasal mucosa about 1 minute after glue injection without the mucosa automatically separating, indicating that the wound has completed preliminary closure; some embodiment formulations have completed firm bonding in about 3 minutes, and the corresponding embodiment adhesive formulation can be matched according to the closing time of the clinical surgical wound.

[0052] See also Figure 3 The histopathological picture shown is seven days after the adhesive was implanted. Under the microscope, adhesive material (▼) is seen adjacent to and surrounding cartilage below the cartilage tissue (▲), and the adjacent cartilage tissue undergoes degeneration due to cartilage removal for modeling. The surface of the cartilage and adhesive material is covered with mucosa, and the epithelium on the surface of the mucosa is incomplete or not fully mature (↗). A small amount of inflammatory cell infiltration is seen in the mucosa (↙), and a small amount of epithelial-like cells and multinucleated giant cells (⊿) are seen around the adhesive material.

[0053] Through histopathological observation after 7D implantation of the adhesive, it was found that the adhesive had only a slight inflammatory reaction to the rabbit nasal septum mucosa, which means that the adhesive has excellent biocompatibility, laying a solid foundation for the clinical promotion of this type of adhesive.

[0054] 5. Water swelling test The water swellability of the adhesive was evaluated by comparing the mass change before and after it was immersed in water.

[0055] The adhesives in Examples 6, 7, and 8 were added to a tetrafluoroethylene mold, cured to form a sheet with a diameter of 1 cm and a thickness of 0.1 mm, and its mass (initial weight) was weighed. It was then immersed in a 0.01M phosphate buffer solution (pH = 7.4) at 37°C. After soaking for a predetermined time, the sample was rinsed with deionized water, and the water on the surface of the sample was dried with filter paper, and then weighed again (the weight of the sample after swelling), and each set of data was repeated three times. The swelling ratio of the adhesive was calculated using the following equation: Swelling ratio (%) = swelling mass - initial weight / initial weight.

[0056] See also Figure 4 , Figure 4 The swelling rate data of the adhesive in Examples 6, 7 and 8. The swelling rate of the adhesive increases with the increase of PEG content. Figure 4It can be seen that the swelling rate of the embodiment basically reaches equilibrium within 4 hours, and the subsequent swelling data has remained stable. The swelling data size is ranked as Example 8>6>7, which is consistent with the order of the amount of polyethylene glycol 600 added in the embodiment from large to small. Although the medical adhesive prepared in the embodiment of the present invention contains polyethylene glycol chains, the adhesive system shows a very low swelling rate, with a maximum of about 38%, while the swelling rate of traditional PEG-based adhesives is about 50% to 400%. This low swelling rate is attributed to the hydrophobic components of the adhesive chain segments and the dense cross-linked polymer network that prevents the entry of water vapor.

[0057] 6. In vitro cell compatibility test According to the requirements of GB / T 16886.5 "Biological Evaluation of Medical Devices" Part 5: In vitro cytotoxicity test, L929 was selected as the test cell line, and the samples of Example 4-8 were formed into films. The sample mass was about 0.3g. After the samples were sterilized, they were placed in culture medium to prepare sample extracts. Five extract samples were prepared for each group. The sample culture medium extracts were used for L929 cell culture. The cells were cultured at 37°C and 5% CO2 for 72 hours. The cell survival rate was then detected by the MTT method, and the results of each group were averaged. The cell compatibility test results of the adhesive in Example 4-8 are shown in Figure 2. Figure 5 shown.

[0058] Table 4 Statistical analysis of cell survival rate data Example Cell viability Reference Positive Control 5.3% Reference Negative control 98.3% Example 4 Adhesive 4 95.3% Example 5 Adhesive 5 93.0% Example 6 Adhesive 6 91.0% Example 7 Adhesive 7 92.4% Example 8 Adhesive 8 91.8% According to the cell survival rate data analysis in Table 4, the materials of Examples 4-8 all showed good cell compatibility, were able to significantly promote cell growth, and the cell survival rates were all above 90%.

[0059] 7. In vitro degradation experiment The reference standards are YY / T 1806.1-2021 Evaluation Method for In Vitro Degradation Performance of Biomedical Materials, Part 1: Degradable Polyesters; GB / T 16886.13 Qualitative and Quantitative Degradation Products of Polymer Medical Devices.

[0060] Among them, the preparation of the phosphate buffer solution (PH=7.4) of the soaking solution: Sorensen slow solution (PH=7.4) prepared with secondary water for analysis and potassium dihydrogen phosphate and disodium hydrogen phosphate in accordance with GB / T 6682. The concentrations of potassium dihydrogen phosphate and disodium hydrogen phosphate are both 1 / 15 mol / L, and the phosphate buffer solution is a mixture of 18.2% (volume fraction) potassium dihydrogen phosphate solution and 81.8% (volume fraction) disodium hydrogen phosphate solution.

[0061] (1) Preparation of test samples The polyurethane adhesives in Examples 2, 4, 5, 6, 7, and 8 were cured into films, and vacuum dried at 45° C. until the film had a constant weight. The film weight was 0.3 g / piece, and five parallels were measured in each group. Phosphate buffer solution (PH=7.4) was added to the sample at a ratio of 50:1 between the volume of the test solution (ml) and the mass of the test sample (g), and the conical flask was sealed; The conical flask was placed in a (70±1)℃ constant temperature incubator for degradation study, and the oscillation frequency was set to 72rmp. Sampling and testing were performed at 0d, 14d, 30d, 60d, 90d, 120d, and 180d. At least three parallel samples and one blank sample were collected at each sampling point, and the final results of the three groups of parallel samples were reported as the average value. The pH value of the degradation solution after sampling was tested simultaneously.

[0062] The weight loss percentage of each group of results was averaged, and the degradation mass loss data was as follows: Figure 6 As shown; the average value of each group of results of the degradation solution pH measurement data is taken, and the pH changes during the degradation process are shown as follows Figure 7 shown.

[0063] Figure 6 The degradation mass loss of the adhesive films of Examples 2, 4, 5, 6, 7, and 8 after 180 days was more than 40%, and the pH of the degradation solution was basically maintained between 7.3 and 6.5 within 180 days. Moreover, the pH of several examples was basically close after 180 days, that is, the degradation products of the adhesive of the present invention had little effect on the surrounding tissue microenvironment, which further confirmed the biocompatibility of the adhesive.

[0064] Degradation curve Figure 7 By comparing the degradation of Example 5 and Example 6, it was found that the introduction of amide bonds not only improved the mechanical strength but also prolonged the degradation time of the film, thereby providing more options for wounds with different healing times; by comparing the degradation curves of Examples 2, 4, and 6, it can be seen that with the increase of the molecular weight of PEG, the degradation rate gradually accelerated; by comparing the degradation curves of Examples 6, 7, and 8, it can be seen that with the increase of the amount of PEG added, the degradation rate gradually accelerated, that is, the degradation rate can be regulated by the content of PEG to adapt to different clinical wound needs.

[0065] In summary, the biodegradable high-strength medical soft tissue adhesive and its preparation method and application provided in the present invention have the following advantages: (1) The raw materials are prepared by a one-pot method, which is simple and convenient to synthesize and is conducive to large-scale production; the combination of polyethylene glycol hydrophilic channels and quaternary ammonium salt ionization centers shortens the curing time and improves the bonding strength.

[0066] (2) By utilizing the diversity of raw materials and the adjustable ratio of soft and hard segments, the multidimensional structure of the basic structure is constructed, and the mechanical properties of the adhesive have a high degree of freedom, which improves the matching degree of biomechanical properties between the adhesive and the application site, reduces internal friction, reduces the pressure of the material on the tissue, and improves the biocompatibility of the material.

[0067] (3) Amino acids and their derivatives are used as raw materials, and the basic amino group of amino acids is used as a catalyst. The non-ionic surfactant effect of polyethylene glycol allows the bulk polymerization of the reaction system to be done in one pot, avoiding the introduction of toxic organic amines and organometallic catalysts, reducing or even eliminating the use of organic solvents for adjusting the polymerization viscosity, and greatly improving the biocompatibility of the adhesive. The fragments of amino acids, peptide raw materials and lysine ethyl ester diisocyanate are coupled to form some peptide-like fragments, which improve the biocompatibility while also improving the efficiency of enzymatic degradation. The change in the amount of polyethylene glycol introduced can further adjust the hydrophilicity of the structural unit of the adhesive, and further regulate the degradation rate in the body, so that the degradation of the adhesive matches the repair process of soft tissue.

[0068] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A biodegradable high-strength medical soft tissue adhesive, made by reacting raw materials, the raw materials comprising a soft segment monomer, a hard segment monomer and a hard segment chain extender, characterized in that: The soft segment monomer is selected from polyethylene glycol or its methoxy derivatives, and its average molecular weight is 300-1000; The hard segment monomer is isocyanate; The hard segment chain extender is a mixture of a hard segment electrically neutral chain extender and a hard segment ionized chain extender; The molar ratio of the soft segment monomer, the hard segment monomer, the hard segment electrically neutral chain extender and the hard segment ionized chain extender is (1-7): (50-95): (14-20): (2-6).

2. The biodegradable high-strength medical soft tissue adhesive according to claim 1, characterized in that: The isocyanate is ethyl lysine diisocyanate and its derivatives or 1,4-diisocyanatobutane and its derivatives.

3. The biodegradable high-strength medical soft tissue adhesive according to claim 1, characterized in that: The hard segment electrically neutral chain extender is an amino acid small molecule chain extender, and the amino acid small molecule chain extender is a mixture of one or more selected from serine, lysine, cystine, serinol, N-acetylneuraminic acid, dipeptide and amino acid ester derivatives; The hard segment ionized chain extender is a quaternary ammonium salt small molecule chain extender, and the quaternary ammonium salt small molecule chain extender is a mixture of one or more selected from bis(2-hydroxyethyl)dimethylammonium chloride, 1,3-dihydroxymethyl-5,5-dimethylhydantoin, 3-(2,3-dihydroxypropyl)-5,5-dimethylimidazolidine-2,4-dione, N-methyldiethanolamine, N-ethyldiethanolamine, 2,3-dihydroxypropyl-trimethylammonium chloride and proiodine.

4. The biodegradable high-strength medical soft tissue adhesive according to claim 1, characterized in that: The raw materials also include a rheology regulator, a foaming catalyst and a stabilizer. The amount of the rheology regulator is 30-50% of the total mass of the soft segment monomer and the hard segment monomer; the amount of the foaming catalyst is 0.8-1.2% of the total mass of the soft segment monomer and the hard segment monomer; the amount of the stabilizer is 0.01-0.05% of the total mass of the soft segment monomer and the hard segment monomer.

5. The biodegradable high-strength medical soft tissue adhesive according to claim 4, characterized in that: The rheology regulator is a mixture of one or more selected from pentafluorobutane, heptafluoropropane, perfluorohexanone, chlorotrifluoropropylene and hexafluorobutene; the stabilizer is a mixture of one or more selected from pyruvic acid, dimethyl sulfoxide, propylene glycol methyl ether acetate, triethyl citrate, sulfuric acid, hydrochloric acid and phosphoric acid.

6. The biodegradable high-strength medical soft tissue adhesive according to claim 4, characterized in that: The foaming catalyst is at least one selected from an organic amine catalyst and an organic metal catalyst, the organic amine catalyst is a mixture of one or more selected from triethylenediamine, bis(dimethylaminoethyl) ether and bis(morpholine) diethyl ether; the organic metal catalyst is a mixture of one or more selected from stannous octoate, dibutyltin dilaurate, organic bismuth salts and organic antimony salts.

7. A method for preparing a biodegradable high-strength medical soft tissue adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: mixing the soft segment monomer, the hard segment chain extender and the hard segment monomer and heating them to react to obtain a mixed reaction system; S2: After the reaction is complete, the temperature is lowered, and a rheology regulator, a foaming catalyst and a stabilizer are added to the mixed reaction system. After uniform mixing, the biodegradable high-strength medical soft tissue adhesive is obtained.

8. The method for preparing a biodegradable high-strength medical soft tissue adhesive according to claim 7, characterized in that: In step S1, the mixing heating temperature is 75-85°C, and the heating reaction time is 1-2h.

9. The method for preparing a biodegradable high-strength medical soft tissue adhesive according to claim 7, characterized in that: In step S2, the cooling temperature is 15-20°C.

10. Use of the biodegradable high-strength medical soft tissue adhesive according to any one of claims 1 to 6 in a functional composite material.

Citation Information

Cited By

  • Bio-based polyurethane hot melt adhesive and preparation method thereof

    CN120310511A

  • Hydrophilic polyurethane and derivative thereof, adhesive hydrogel prepared by derivative and application of adhesive hydrogel

    CN121021787A

  • High-performance degradable biomedical tissue adhesive as well as preparation method and application thereof

    CN122399086A

  • High-performance degradable biomedical tissue adhesive and preparation method and application thereof

    CN122399086B